Back Cover: Mechanistic Insight into the Conversion of Tetrose Sugars to Novel α‐Hydroxy Acid Platform Molecules (ChemCatChem 2/2013). Issue 2 (30th January 2013) - Dusselier, Michiel; Van Wouwe, Pieter; de Clippel, Filip; Dijkmans, Jan; Gammon, David W.; Sels, Bert F.
<x xml:space="preserve">Abstract</x> How to win with tin! The cover picture shows the ability of dissolved tin, the 50th element of Mendeleev's periodic table, to catalyze the conversion of tetrose sugars in alcoholic media via a cascade reaction: an isomerization, two retro‐Michael reactions, a hemi‐acetalization, a 1, 4‐addition, and a 1, 2‐hydride shift. In their Full Paper on p. 569 ff., M. Dusselier, B. F. Sels et al. report on the mechanistic implications of the tetrose transformation with Sn, leading to new four‐carbon‐backbone α‐hydroxy esters such as methyl vinylglycolate (MVG) and methyl‐4‐methoxy‐2‐hydroxybutanoate (MMHB), of use in bio‐derived polyesters. In situ NMR spectroscopy, deuterium labeling, and control experiments with intermediates revealed the individual pathways in which the kinetic competition between the 1, 4‐addition and 1, 2‐hydride shift is key to the product outcome.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>